2020
DOI: 10.1002/hbm.25324
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cannabis use disorder with cognition, brain structure, and brain function inAfrican Americans

Abstract: Although previous studies have highlighted associations of cannabis use with cognition and brain morphometry, critical questions remain with regard to the association between cannabis use and brain structural and functional connectivity. In a cross‐sectional community sample of 205 African Americans (age 18–70) we tested for associations of cannabis use disorder (CUD, n = 57) with multi‐domain cognitive measures and structural, diffusion, and resting state brain‐imaging phenotypes. Post hoc model evidence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 91 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…Our sample was relatively young (i.e., below 25), and while most had a mild to moderate CUD, none of them were seeking treatment. Indeed, a study including slightly older (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) individuals with a CUD history, found more widespread FA differences 24 and another study showed stronger relations between white matter microstructure and cannabis exposure in older users. 21 The clear CUD research gap needs to be addressed in future studies, including assessments in clinical populations and investigations of distinct vulnerability periods across the lifespan.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our sample was relatively young (i.e., below 25), and while most had a mild to moderate CUD, none of them were seeking treatment. Indeed, a study including slightly older (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) individuals with a CUD history, found more widespread FA differences 24 and another study showed stronger relations between white matter microstructure and cannabis exposure in older users. 21 The clear CUD research gap needs to be addressed in future studies, including assessments in clinical populations and investigations of distinct vulnerability periods across the lifespan.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, others reported differences in weekly cannabis users compared to non‐using controls in the forceps minor (higher FA and lower RD 20 ; lower FA 21 ; higher MD 22 ), superior longitudinal fasciculus (SLF; lower FA 23 ), bilateral hippocampus (lower FA 23 ), the uncinate fasciculus (lower FA and higher MD 22 ) and the frontal part of the corpus callosum (higher MD 18 ). In individuals with a diagnosed CUD compared to non‐using controls, one study found lower FA in various parietal and temporal white matter bundles, 24 while another study did not find any significant group differences 25 . Moreover, a 2‐year longitudinal study in weekly cannabis users reported more widespread alterations over time in various frontal, temporal and parietal white matter tracts, which covaried with cannabis exposure over time 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to achieve this, this study only included participants with a confirmed diagnosis of CUD, assessed by the DSM -5. Only a few studies have examined CUD specifically and show poorer performance on cognitive tasks ( Koenis et al, 2021 ), lower academic achievement ( Hooper et al, 2014 ) and neural alterations ( Ashtari et al, 2011 ; Koenis et al, 2021 ) in individuals with CUD. However, the results are also not directly comparable as two use long periods of abstinence (6 months+, Ashtari et al, 2011 ; Hooper et al, 2014 ) and one has an older sample (mean age: 40, Koenis et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these studies have long periods of abstinence (6 months+) and may not be representative of the recent effects of chronic cannabis use. Indeed, Koenis et al (2021) measure more recent effects; however, the average age of their sample is 40 and their study does not reflect the results from young adults, who have the highest prevalence of cannabis use (UNODC, 2020).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation